PERAN INSENTIF DALAM MEMEDIASI PENGARUH EMPLOYEE INVOLVEMENT DAN SELF-EFFICACY TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN TASIKMALAYA - Yurahmi, Fahmi; Sudiarti, Sri; Wahyu Fitriadi, Budhi (JURNAL EKONOMI PERJUANGAN, 2025)
This study aims to provide an overview and analyze the influence of Employee Involvement and Self-Efficacy on Employee Performance with Incentives as a mediating variable at the Secretariat of the Tasikmalaya Regency DPRD. This study employs a quantitative approach using a survey method and Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique with the assistance of SmartPLS 4 software. The sample consists of 30 respondents using a saturated sampling technique. The results indicate that Employee Involvement and Self-Efficacy significantly influence Incentives. Additionally, Incentives also significantly influence Employee Performance. Furthermore, Incentives were found to significantly mediate the influence of Employee Involvement and Self-Efficacy on Performance. These findings confirm that high levels of employee involvement and self-efficacy can enhance performance when accompanied by appropriate incentives as a form of organizational recognition.